Supranormal thymic output up to 2 decades after HIV-1 infection. (13th March 2016) - Aguilera-Sandoval, Christian R.; Yang, Otto O.; Jojic, Nebojsa; Lovato, Pietro; Chen, Diana Y.; Boechat, Maria Ines; Cooper, Paige; Zuo, Jun; Ramirez, Christina; Belzer, Marvin; Church, Joseph A.; Krogstad, Paul
Abstract : Objectives: AIDS is caused by CD4 + T-cell depletion. Although combination antiretroviral therapy can restore blood T-cell numbers, the clonal diversity of the reconstituting cells, critical for immunocompetence, is not well defined. Methods: We performed an extensive analysis of parameters of thymic function in perinatally HIV-1-infected ( n  = 39) and control ( n  = 28) participants ranging from 13 to 23 years of age. CD4 + T cells including naive (CD27 + CD45RA + ) and recent thymic emigrant (RTE) (CD31 + /CD45RA + ) cells, were quantified by flow cytometry. Deep sequencing was used to examine T-cell receptor (TCR) sequence diversity in sorted RTE CD4 + T cells. Results: Infected participants had reduced CD4 + T-cell levels with predominant depletion of the memory subset and preservation of naive cells. RTE CD4 + T-cell levels were normal in most infected individuals, and enhanced thymopoiesis was indicated by higher proportions of CD4 + T cells containing TCR recombination excision circles. Memory CD4 + T-cell depletion was highly associated with CD8 + T-cell activation in HIV-1-infected persons and plasma interlekin-7 levels were correlated with naive CD4 + T cells, suggesting activation-driven loss and compensatory enhancement of thymopoiesis. Deep sequencing of CD4 + T-cell receptor sequences in well compensated infected persons demonstrated supranormal diversity, providing additional evidence of enhanced thymic output. Conclusion: Despite up to two decades of infection, many individuals have remarkable thymic reserve to compensate for ongoing CD4 + T-cell loss, although there is ongoing viral replication and immune activation despite combination antiretroviral therapy. The longer term sustainability of this physiology remains to be determined. Abstract : Supplemental Digital Content is available in the text